Green Accounting, Carbon Emission Disclosure And Its Impact On Company Value - Dyah Aruning Puspita; Nadela Syahma; Sugeng Hariadi (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
A company's performance achievements, which raise the company's value through an increase in stock prices on the Indonesia Stock Exchange (IDX), indicate the degree of stakeholder faith in management.. This study tries to investigate the impact of carbon emission disclosure and green accounting on corporate value. The aims of study to ascertain the impact of carbon emission disclosure and green accounting on company value. Descriptive and verification research methods were used in this quantitative investigation. The population in this study is Palm Oil Issuer Companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2022 period. And the sample used is 9 companies according to the selected criteria. Multiple regression and descriptive analysis are used in this study's analysis method. The study's findings suggest that green accounting significantly affects a company's value and that reporting carbon emissions has a significant impact on that value.This suggests that a company's worth will rise in tandem with its growing use of green accounting, and that disclosure of carbon emissions has a big impact on that value. Put another way, a company's worth tends to rise in proportion to the amount of information it discloses about its carbon emissions